Exploring the impact of AI on unemployment for people with disabilities: do educational attainment and governance matter? - Anis Omri; Anis Omri; Henda Omri; Hatem Afi (Frontiers in Public Health)
The current study investigates the impact of artificial intelligence (AI) on unemployment among people with disabilities, focusing on the mediating role of education and the moderating effect of governance quality. Using panel data from 27 high-tech developed countries between 2006 and 2022, the findings reveal a nuanced relationship where AI initially increases unemployment among people with disabilities due to automation and skill mismatches. However, advanced education mitigates this effect, significantly improving employability by equipping individuals with market-relevant skills. Governance quality plays a critical role in this dynamic, amplifying AI’s positive impact on education while, paradoxically, intensifying its negative effects on unemployment when governance frameworks are weak or misaligned. These findings underscore the importance of robust governance structures and targeted educational initiatives to harness AI’s potential in fostering inclusive labor markets. Policymakers should align AI investments with governance reforms and education systems to ensure equitable employment opportunities for people with disabilities.